Correction of Neurological Disorders in Children with Respiratory Diseases. (Eurasian Medical Research Periodical, 2022)
Children who have suffered perinatal lesions of the nervous system are more likely to suffer from respiratory diseases. This, in turn, requires antihypoxic, neurotrophic therapy aimed at normalizing cerebral and general circulation. The inclusion of the drug oxybral in the complex of treatment contributed, along with the improvement of neurological symptoms, to the fastest recovery of children with respiratory diseases.